REFORMASI PEMIDANAAN KORUPSI KORPORASI MELALUI KONSTRUKSI MODEL DEFFERED PROSECUTION AGREEMENT BERBASIS KEADILAN SOSIAL DI INDONESIA - Pravidjayanto, Mochammad Rafi; Haq, Neha Hifa; Alfatoni, Muhammad Aqil (Jurnal Yuridis, 2025)
Corruption is the main factor in doing business in Indonesia. The subject of corporate law plays a major role in the rate of economic growth in Indonesia, thus causing a tendency for corruption crimes by corporations. Enforcement through penal channels imposed on corporations reaps problems, such as a decline in public trust which results in a decrease in corporate income which has implications for mass termination of employment. The purpose of this paper is to examine the opportunities and challenges of implementing the Deferred Prosecution Agreement (DPA) or suspension of prosecution in the enforcement of corporate crimes carried out with a non-penal approach based on John Rawls' social justice. This study uses a juridical-normative method with conceptual, legislative, and comparative approaches. The results of the paper show that the importance of the implementation of the DPA and its potential application lies in the prosecutor as the ruler of the case by applying the principle of opportunity. The challenges in its implementation are related to the differences in the state legal system that uses the DPA mechanism, the shift in the principle of enforcing corruption crimes as extra ordinary crimes from primum remedium to ultimum remedium. The recommendations offered include the urgency to establish a special law that regulates the DPA mechanism in Indonesia as a consequence of the civil law legal system, adding a mechanism if the corporation has good faith in submitting an agreement with the prosecutor through Self-Report and opportunities to improve corporate governance.